Multipliers of Laplace Transform Type for Laguerre and Hermite Expansions - de Napoli, Pablo Luis (2011)
We present a new criterion for the weighted Lp-Lq boundedness of multiplier operators for Laguerre and Hermite expansions that arise from a Laplace–Stieltjes transform. As a special case, we recover known results on weighted estimates for Laguerre and Hermite fractional integrals with a unified and simpler approach.